2000
DOI: 10.1074/jbc.m003410200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Activity of Human p23, a Heat Shock Protein 90 Co-chaperone

Abstract: p23 is a co-chaperone for the heat shock protein, hsp90. This protein binds hsp90 and participates in the folding of a number of cell regulatory proteins, but its activities are still unclear. We have solved a crystal structure of human p23 lacking 35 residues at the COOH terminus. The structure reveals a disulfide-linked dimer with each subunit containing eight ␤-strands in a compact antiparallel ␤-sandwich fold. In solution, however, p23 is primarily monomeric and the dimer appears to be a minor component. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
147
2
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(161 citation statements)
references
References 33 publications
8
147
2
4
Order By: Relevance
“…Using computational modeling studies, we showed that gedunin can be successfully docked into the p23 structure, and three amino acids (Thr-90, Ala-94, and Lys-95) possibly mediate noncovalent interactions with gedunin. The crystal structure of p23 dimer reported by Weaver et al (32) showed that the surface of p23 molecule exhibits a solvent-accessible cavity surrounded by polar amino acids, whereas the floor of the cavity contains nonpolar hydrophobic amino acids, which appear to provide a ligand-binding site on the surface of p23. Utilizing molecular modeling and docking software, we observed that gedunin docks into this ligand-binding site, forms hydrogen bonds with Thr-90 and Lys-95, and maintains hydrophobic interactions with Ala-94.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using computational modeling studies, we showed that gedunin can be successfully docked into the p23 structure, and three amino acids (Thr-90, Ala-94, and Lys-95) possibly mediate noncovalent interactions with gedunin. The crystal structure of p23 dimer reported by Weaver et al (32) showed that the surface of p23 molecule exhibits a solvent-accessible cavity surrounded by polar amino acids, whereas the floor of the cavity contains nonpolar hydrophobic amino acids, which appear to provide a ligand-binding site on the surface of p23. Utilizing molecular modeling and docking software, we observed that gedunin docks into this ligand-binding site, forms hydrogen bonds with Thr-90 and Lys-95, and maintains hydrophobic interactions with Ala-94.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it appears that the C-terminal 35 amino acids are essential for gedunin-p23 binding, which suggests that the unstructured C-terminal tail stabilizes gedunin binding to the identified pocket. The ligand-binding cleft, along with other amino acids in this vicinity, compose the Hsp90-binding site on the surface of p23 (32,44), and gedunin binding to p23 appears to alter the topology of this region thus disrupting the p23-Hsp90 interaction. Data in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second constraint is the requirement for the cleavage site to occupy the substrate-binding pocket. In the case of p23, the length of the C-terminal region spans 49 residues and is unstructured (34), which theoretically allows it to reach either catalytic center. However, in the model we proposed, the C-terminal binds the closest active site.…”
Section: Discussionmentioning
confidence: 99%